Alterations of gut virome with close interaction in the progression of estrogen deficiency-induced osteoporosis - Yueqi Chen; Chuan Yang; Zihan Deng; Tingwen Xiang; Jiulin Tan; Jianzhong Xu; Dong Sun; Fei Luo (Gut Microbes)
Previous research has established a link between gut microbiota and osteoporosis (OP) advancement. However, there remains a limited understanding of the crucial contribution of the gut virome in the onset and progression of OP. We employed metagenomic shotgun sequencing and gut virome sequencing to process the ovariectomy (OVX)-induced OP murine model, which revealed significant disparities in bacteriome and virome compositions between subjects with OP and healthy controls. One hundred and seventy-four altered viral strains were identified to participate in the multifaceted regulation of bone loss, involving immune modulation, microbial metabolic activity, and intricate host-virus dynamics. Our findings suggested that the gut virome may influence bone metabolism, potentially altering the balance of bone-modulating compounds like short-chain fatty acids. This comprehensive analysis of the gut virome in OP highlighted the diagnostic potential of combined gut viral and bacterial biomarkers for OP.